Paraguay : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2011)
Paraguay weathered the global economic crisis well, supported by an appropriate policy response. The strong rebound of economic growth has given rise to overheating pressures. Policies need to adjust further to ensure a soft landing of the economy. The banking system remains sound, but there is a need to guard it against emerging risks. The monetary policy framework should be strengthened further to support the move to an inflation-targeting (IT) regime. Higher tax revenues are needed to address important deficiencies in infrastructure and basic social services.